HUBUNGAN ANTARA AGRESIFITAS DENGAN KESEHATAN MENTAL SISWA KELAS VIII SMPN 2 WAGIR - Bambang Wahono (Universitas Islam Balitar, 2016)
This study examines relationship between aggressiveness and mental health of students. This study applied correlational design. Conducted at SMPN 2 Wagir, Malang, this study assigned 216 sample of the 10thgraders. Data were analyzed using statistical and non-statistical models. The study discovered that there was a significant relationship between variable X and Y. Elaborated in correlational statement, the study concluded: (a) high aggressiveness of students does not mean that students ’ mental health is low (bad), (b) low mental health of students does not mean that aggressiveness is high, and (c) moderate aggressiveness of students probably means students ’ mental health is also moderate.